1995
DOI: 10.1126/science.270.5236.593
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins and Neuronal Plasticity

Abstract: There is increasing evidence that neurotrophins (NTs) are involved in processes of neuronal plasticity besides their well-established actions in regulating the survival, differentiation, and maintenance of functions of specific populations of neurons. Nerve growth factor, brain-derived neurotrophic factor, NT-4/5, and corresponding antibodies dramatically modify the development of the visual cortex. Although the neuronal elements involved have not yet been identified, complementary studies of other systems hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
1,040
0
21

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,833 publications
(1,092 citation statements)
references
References 105 publications
31
1,040
0
21
Order By: Relevance
“…In addition, recent results indicate that neurotrophins are also involved in the processes of neural plasticity (Thoenen, 1995). Here we have shown that NGF may in¯uence the program of gene expression which is under control of the cAMP signalling pathway.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, recent results indicate that neurotrophins are also involved in the processes of neural plasticity (Thoenen, 1995). Here we have shown that NGF may in¯uence the program of gene expression which is under control of the cAMP signalling pathway.…”
Section: Discussionmentioning
confidence: 51%
“…BDNF influences neuronal differentiation in development, as well as synaptic plasticity and neuronal survival in adulthood (Thoenen, 1995). Several results suggest that it may play a role in the pathophysiology of depression (Duman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Mice overexpressing BDNF in the postnatal brain show a precocious critical period for ODP 18,19 . The prevailing hypothesis 8,17,20,21 has been that competition for limited amounts of BDNF, which acts on TrkB receptors, is the effector of activity-dependent plasticity in the cortex, and the conventional explanation for ODP is that the deprived eye fails to activate cortical cells as well as the open eye, thereby failing to stimulate them to release sufficient BDNF to sustain the deprived-eye pathway.…”
mentioning
confidence: 99%